2017
DOI: 10.1016/j.jacc.2017.08.013
|View full text |Cite
|
Sign up to set email alerts
|

Protein Phosphatase Inhibitor-1 Gene Therapy in a Swine Model of Nonischemic Heart Failure

Abstract: BACKGROUND Increased protein phosphatase-1 (PP1) in heart failure (HF) induces molecular changes deleterious to the cardiac cell. Inhibiting PP1 through the overexpression of a constitutively active inhibitor-1 (I-1c) has been shown to reverse cardiac dysfunction in a model of ischemic HF. OBJECTIVES We sought to determine the therapeutic efficacy of a re-engineered adeno-associated viral vector carrying I-1c (BNP116.I-1c) in a preclinical model of nonischemic HF, and to assess thoroughly the safety of BNP11… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 35 publications
1
16
0
Order By: Relevance
“…Given the enormous clinical need for the development of improved treatment options of both inherited and acquired cardiovascular diseases, it is not surprising that extensive preclinical research has been performed to test AAV vectors to treat cardiovascular diseases, most prominently heart failure. These intense efforts resulted in a plethora of successful studies, especially in rodents 4750 , but also in pre-clinically relevant large animal models 5155 Based on extensive pre-clinical studies focused on delivering the cardiac isoform of the sarcoplasmic reticulum calcium ATPase pump, a dose escalating First in Man clinical study was initiated in patients with severe heart failure 56 . Phase 1 of the CUPID trial demonstrated the safety of delivering an AAV1 vector encoding SERCA2a via antegrade intracoronary infusion and indicated potential clinical benefit at a dose of 10 13 vg 57, 58 .…”
mentioning
confidence: 99%
“…Given the enormous clinical need for the development of improved treatment options of both inherited and acquired cardiovascular diseases, it is not surprising that extensive preclinical research has been performed to test AAV vectors to treat cardiovascular diseases, most prominently heart failure. These intense efforts resulted in a plethora of successful studies, especially in rodents 4750 , but also in pre-clinically relevant large animal models 5155 Based on extensive pre-clinical studies focused on delivering the cardiac isoform of the sarcoplasmic reticulum calcium ATPase pump, a dose escalating First in Man clinical study was initiated in patients with severe heart failure 56 . Phase 1 of the CUPID trial demonstrated the safety of delivering an AAV1 vector encoding SERCA2a via antegrade intracoronary infusion and indicated potential clinical benefit at a dose of 10 13 vg 57, 58 .…”
mentioning
confidence: 99%
“…The results demonstrated in the animal model that the gene therapy was safe and significantly reversed heart failure by 25 percent in the left ventricle and by 20 percent in the left atrium. The treatment group also showed a ten percent decrease in heart enlargement, a common symptom of heart disease [29]. Carfostin will soon undergo clinical trials.…”
Section: Protein Phosphatasementioning
confidence: 89%
“…Although additional research would be required for such translation, it is important to note that epicardial access and interventions by minimally invasive thoracoscopic surgery or a subxiphoidal approach are already feasible and safe, and device implantation for cardiac rhythm management is currently one of the mainstays of treatment. In addition, recent clinical trials have demonstrated that human cardiac gene therapy is feasible and safe (43)(44)(45), and new human cardiac gene therapeutic studies are being planned (46).…”
Section: Discussionmentioning
confidence: 99%